Different pathways for protein degradation by the FtsH/HflKC membrane-embedded protease complex: an implication from the interference by a mutant form of a new substrate protein, YccA - Kihara, Akio; Akiyama, Yoshinori; Ito, Koreaki (Journal of molecular biology, 1998)
Escherichia coli FtsH (HflB) is a membrane-bound and ATP-dependent zinc-metalloproteinase, which forms a complex with a pair of periplasmically exposed membrane proteins, HflK and HflC. It is the protease that degrades uncomplexed forms of the SecY subunit of protein translocase. Here, we characterized a new class of SecY-stabilizing mutation on the E. coli chromosome. The mutation (yccA11) is an internal deletion within a gene (yccA) known as an open reading frame for a hydrophobic protein with putative seven transmembrane segments. The YccA protein was found to be degraded in an FtsH-dependent manner in vivo and in vitro, whereas the YccA11 mutant protein, lacking eight amino acid residues within the amino-terminal cytoplasmic domain, was refractory to the degradation. The yccA11 mutation exhibited partial dominance when overexpressed. Cross-linking, co-immunoprecipitation, and histidine tagging experiments showed that YccA11 as well as YccA can associate with both the FtsH and the HflKC proteins. Thus, the mutant YccA protein appeared to compete with SecY for recognition by the FtsH proteolytic system and the residues deleted by the yccA mutation are required for the initiation of proteolysis by FtsH. Interestingly, the inhibitory action of YccA11 was mediated by HflKC, since the deletion of hflK-hflC suppressed the yccA11 phenotype. The yccA11 mutation stabilized subunit a of the proton ATPase F0 segment as well, but not the CII protein of bacteriophage lambda or the sigma 32 protein. From these results we suggest that there are at least two pathways for FtsH-dependent protein degradation, only one of which (probably for membrane proteins) is subject to the HflKC-dependent interference by the YccA11 mutant substrate.